Getting out : historical perspectives on leaving Iraq - Mills, Nicolaus; Walzer, Michael (Book collections on Project MUSE., 2009)
In Getting Out, a diverse cast of noted scholars and journalists considers how the United States might leave Iraq by examining seven historical case studies on how to and how not to withdraw from occupied territory.